Kinetic perspectives for the degradation of oxacillin: A penicillanic acid derivative - Sahu, Yuv Raj; Chaudhary, Narendra Kumar; Bhattarai, Ajaya (Edelweiss Applied Science and Technology, 2024)
Oxidation of oxacillin, a penicillanic acid derivative, has been predicted by monoperiodatocuprate [MPC (III)] at 25°C with 0.10 mol dm-3 ionic strength, in an aqueous alkaline medium by UV/Visible spectrophotometric analysis, for which 1:4 stoichiometry of oxacillin: MPC (III) is visible. The appearance of a sharp peak by the spectrophotometer confirmed the formation of the complex. The reaction products have been recognized using spectral reports from the FT-IR, LC-MS, melting point, and other spot tests. A pseudo-first-order reaction has been confirmed for the oxidant, fractional order for the substrate, and alkali, even though periodate claimed a delaying effect due to the accumulation of periodate ions from both potassium periodate and monoperiodatocuprate as a common ion effect. The primary active species in the alkaline medium [Cu(H2IO6)(H2O)2] was discovered to be monoperiodatocuprate [MPC (III)]. To figure out the activation and thermodynamic parameters, it is helpful to know the uncatalyzed rate constants, the slow step rate constants, and the equilibrium constants. We have evaluated the dependence of reaction rates on different temperatures. We have calculated rate constants using absorbance data collected from the UV/visible spectrophotometer. We have thoroughly examined the potential rate constant derivation and a plausible mechanism that could explain the experimental findings.